Formação musical e a inclusão social de crianças e jovens na Orquestra Criança Cidadã - Alves, Marcelo Jorge Cabral de Mello Dantas (2012)
The present work is about the Orquestra Criança Cidadã (Child Citizen Orchestra), a nongovernmental organisation that assists children and youngsters aged 4 to 20 who live in the Coque neighbourhood in Recife, Pernambuco. The main purpose of this study is to understand the relationship between the music education received and the social inclusion of these children and youngsters. In order to fulfill this aim, case study method was chosen as the means of collecting data. The results revealed the influence of a social music education on the lives of these children and youngsters, especially regarding their personal relationships and their development as citizens.